"It's Like Shouting to a Brick Wall": Normative Whiteness and Racism in the European Parliament. Issue 1 (19th February 2023) - KANTOLA, JOHANNA; ELOMÄKI, ANNA; GAWEDA, BARBARA; MILLER, CHERRY; AHRENS, PETRA; BERTHET, VALENTINE
Abstract : There is a notable gap in the academic literature on racism within European Union institutions. This article scrutinizes racism and normative whiteness in one of these institutions—namely, the European Parliament. The article asks how European whiteness, as a norm, is related to and sustains racism in the European Parliament and how this affects efforts to tackle racism and formulate internal antiracist practices within the institution. The research material consists of interviews, parliamentary ethnography, and official document data, and the empirical analysis is divided into three levels: individual, political group, and parliamentary. An important contribution is to demonstrate the techniques of reproducing whiteness as an institutional norm and racialized power relations in the European Parliament. This avoids linking racism to only the actions and attitudes of individuals and enables the article to address how racism is reproduced through the Parliament as an institution.